Fluxo de carrapatos entre ambientes e animais na fazenda Capim-Branco, Uberlândia-MG: Considerações epidemiológicas - Siqueira, Samantha Maciel de (2017)
Natural ecosystems are under severe human pressure which promotes fragmentation and destruction of large native areas. These changes favor situations unfit for the parasite leading to the emergence or reemergence of infectious/parasitic diseases. Consequently, epidemiological studies of ticks between animals and environment have become important, helping to identify the role of these vectors in the dispersion of pathogens. The samples were collected in the Experimental Farm Capim Branco - Uberlândia, MG, in 2015 to 2017. For the collection free living ticks use a dragging flag and CO2 traps and for the animals used visual inspection. In rural areas the highest prevalence was of Amblyomma sculptum, followed by Rhipicephalus microplus and Amblyomma dubitatum. In the sheep area collected R. microplus and Amblyomma spp., with predominance of A. sculptum nymphs in winter. In forest areas A. sculptum and A. dubitatum were the most frequent although the A. sculptum was higher in the “ribeirinha” area the semideciduous area. Still in the forest it found in smaller quantity R. microplus, Ixodes loricatus and Amblyomma longirostre. Observed a greater efficiency for the drag in the aggregate of larvae while the ice trap was more suitable for nymphs and adults of the Amblyomma spp. It has also been seen that forest areas are constantly more infested than rural areas. The majority ticks of the cattle were R. microplus, but the presence of A. sculptum was frequently observed in less quantity. The parasitism on cattle by tick is not accidental. Dermacentor nitens, A. sculptum and R. microplus were found in horses, respectively, following the prevalence. The dogs presented Rhipicephalus sanguineus and A. sculptum and finally, in non volant small mammals the presence of I. loricatus was dominant, but A. sculptum was not discarded. No ticks were found in sheep. Consequently it is noted that the A. sculptum is present in different environments as in cattle, horses, dogs and small mammals. It suggests to be an important tick in the Cerrado and the most common vector associated with spotted fever in Brazil.